ALTERATIONS IN HEMATOLOGICAL INDICES IN ANTENATAL AND POSTNATAL MOTHERS WITHIN KERKUK PROVINCE, IRAQ - Azeez, Sarah T.; Bayatli, Feedan J.; Bazzaz, Ayoub A.; Chelebi, Noorhan A. (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: The purpose of this study is to examine changes in hemoglobin, packed cell volume, white blood cells, and platelet counts in Iraqi women from Kirkuk Province during the prenatal and postnatal phases. Methods: During the course of a year, 600 women attended Azadi Hospital in Kirkuk, including 300 pregnant women in the third trimester and 300 postpartum women. An automated analyzer was used to collect and analyze blood samples, and the outcomes were contrasted with those of a control group of 60 university students who were not pregnant. Results Hematological parameters showed notable alterations. During pregnancy, hemoglobin and packed cell volume dropped, but after delivery, they rose (p < 0.022). During pregnancy, the white blood cell count was significantly greater (p < 0.001), and it continued to rise after delivery. There was no discernible change in the platelet count. Instead of clinical situations, these deviations were ascribed to normal physiological processes. Novelty: This study contributes to better health monitoring and risk assessment for maternal care by shedding light on the typical hematological alterations that occur in Iraqi women throughout pregnancy and the postpartum phase.